Yard birds : the lives and times of America's urban chickens - Levy, Philip, 1963- (University of Virginia Press, 2023)
"This book traces the surprisingly long history of chickens as part of the American cityscape and illuminates the resurgent cultural phenomenon of the backyard chicken, taking readers to nineteenth-century urban poultry shows, along a "Tour de Coops," inside zoning battles, and into religious rituals"--